SPECIES DIVERSITY OF UNDERGROWTH MEDICINAL PLANTS IN PHU POE COMMUNITY FOREST, KALASIN PROVINCE, THAILAND - Homchuen, S.; Pichaensoonthon, C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Phu Poe Community Forest, a young recovery forest in Tumbon Naboan, Ampur Kammuang, Kalasin Province, Thailand consists of a compound dry dipterocarp forest with mixed deciduous forest. The main objective of this study is to compile a checklist of undergrowth plants in this forest and explore their ethnobotanical information. The belt transect method, 10 meters wide with 1,200 meters long from the ground level to the top of the mountain (253-426 msl), was applied for the plant collection. There were altogether 16 belt transects with a distance of an interval about 250 meters each. The plant specimens were collected from July to October 2003. The general morphology and habitat of the plants collected with their uses (if any) were documented. A total of 101 species (72 genera in 49 families) were enumerated with one species each of non-seeded plant and the gymnosperm, 20 species (11 genera in 7 families) of the monocotyledons and 79 species (59 genera in 40 families) of the dicotyledons. From all the specimens collected, the number of the family Zingiberaceae was the greatest (10 species) used for medicinal plants. Though this forest has just been discovered, the species richness was so high and from the study one rare species (Stahlianthus campanulatus) was found. Acknowledgements: Khon Kaen University, Thailand provided funding and Naboan Villagers provided the information.